Prairie Rattlesnake Envenomation in 27 New World Camelids. (26th July 2013) - Sonis, J.M.; Hackett, E.S.; Callan, R.J.; Holt, T.N.; Hackett, T.B.
Abstract : Background: Morbidity and case fatality from rattlesnake envenomation is regionally specific because of variability in relative toxicity of the species of snake encountered. A previous report of rattlesnake envenomation in New World camelids (NWC) from the western coastal United States documented high case fatality rates and guarded prognosis for survival. Hypothesis/Objectives: To describe clinical findings, treatments, and outcome of NWC with prairie rattlesnake ( Crotalus viridis viridis ) envenomation in the Rocky Mountain region of the United States. Animals: Twenty‐seven NWC admitted to the Colorado State University Veterinary Teaching Hospital for evaluation of acute rattlesnake envenomation between 1992 and 2012. Methods: Medical records of NWC evaluated for rattlesnake envenomation as coded by the attending clinician and identified by a database search were reviewed retrospectively. Month of admission, signalment, area of bite, clinical and clinicopathologic data, treatments, and outcome were recorded. Results: Twenty‐five llamas and 2 alpacas were admitted for envenomation. Llamas were overrepresented compared to hospital caseload. The face was the most common site of envenomation, observed in 96% of recorded cases. Presenting clinical signs included fever, tachypnea, tachycardia, and respiratory distress. Nine animals required a tracheotomy. Median hospitalization time was 3 days and overall survival rate was 69%. Conclusions and Clinical Importance: Case fatality rate for prairie rattlesnake envenomation in NWC was lower than that reported in the Western coastal region of the United States and similar to that reported for prairie rattlesnake envenomation in horses.